THE LIFESTYLE OF STRAIGHTEDGE AMERICAN AS SEEN IN FOUR SONGS OF GOOD CLEAN FUN BAND - SUDRAJAD, RISANG (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key Words: Subculture, Straightedge, Movement, Semiotic, Sociology of Literature, Good Clean Fun Subculture is a part of the society. Sociologically, a subculture is a group of people who have their own attitudes and beliefs that are different from their parent culture. Subculture is also a form of resistance against the society. The subculture resistance can be seen through the various movements that they make such as by using song lyric. One example of subculture movement is by the messages contained in a song lyric. To analyze the correlation between song lyric and society especially subculture, Semiotic and Sociology of Literature theories are applied in the research. we. Semiotics is the study of message or meaning behind an object. Whereas the Sociology of Literature is the study of the relationship between literary work and the society. This study will examine the Straightedge American lifestyle which is reflected in the four songs of Good Clean Fun.In this study, the data were obtained through the lyrics of four songs from the Good Clean Fun band. The selection of Good Clean Fun as an object of analysis based on the background the band itself which is vegan straightedge band. This study also describes the Straightedge American lifestyle based the movement that they make. Straightedge American lifestyle can be seen through the songs that become the object of this study. There are four Straightedge American core values that become the basis of their movement. Those core values are no drugs, no alcohol, no casual sex and veganism.The writer also suggests the further researchers to use counter hegemony theory because straightedge also deals with the resistance to the mainstream lifestyle in society. This theory can be used to how straightedge can be the counter hegemony of society especially in young people lifestyle.